Answer :

Put x = a cosθ


tan–1


tan–1


tan–1


Rationalising it


tan–1


tan–1


tan–1


tan–1


Cos θ = 1 – 2 sin2 and sinθ =


1 – cosθ = 2 sin2


= tan–1


= tan–1


= tan–1(tan)


=


But θ = cos–1


The given equation simplification to cos–1 .


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Prove the followiMathematics - Board Papers

Solve the followiMathematics - Board Papers